2008
DOI: 10.1513/pats.200709-153et
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NETT in Emphysema Research

Abstract: Lung volume reduction surgery (LVRS) is one of a long lineage of surgical approaches to emphysema. The reintroduction of this operation in the mid-1990s led to great controversy over the value of the procedure and its long-term outcomes. The National Emphysema Treatment Trial (NETT) represented an historical scientific collaboration of the National Institutes of Health (NIH), the Centers for Medicare and Medicaid Services (CMS), and the Agency for Health Research and Quality (AHRQ). NETT was designed primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Over half of the included studies were from larger cohort studies and subsequent retrospective/cross-sectional analysis. The nature of these cohorts introduces heterogeneity in the types of patients recruited, ie, lung cancer screening studies (NELSON), 52 alpha one cohorts, 53 COPD (eg, COPDGene, KOLD 15 , 54 ) and end-stage disease (eg, NETT). 55 The consistency of direction of the relationship between density and lung function across diverse patient groups is reassuring and suggests that density could be a valid surrogate outcome across the spectrum of disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of the included studies were from larger cohort studies and subsequent retrospective/cross-sectional analysis. The nature of these cohorts introduces heterogeneity in the types of patients recruited, ie, lung cancer screening studies (NELSON), 52 alpha one cohorts, 53 COPD (eg, COPDGene, KOLD 15 , 54 ) and end-stage disease (eg, NETT). 55 The consistency of direction of the relationship between density and lung function across diverse patient groups is reassuring and suggests that density could be a valid surrogate outcome across the spectrum of disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologists did not follow a published protocol such as that of the National Emphysema Treatment Trial (NETT) to grade emphysema. [33] Although this may have reduced precision, reproducibility for moderate or severe emphysema was high and this approach likely increased clinical applicability since the interpretations followed standard academic clinical practice. Moreover, using an identical method this group of radiologists found that mild, moderate and severe emphysema predicted lung cancer and mortality from COPD in older smokers undergoing CT lung cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary rehabilitation provides substantial benefits for patients with severe COPD, including increased exercise capacity and decreased dyspnea. Although many patients never participate in this therapy modality, it is certainly less costly than surgery and associated with less immediate morbidity and mortality 27 .…”
Section: Discussionmentioning
confidence: 99%